Impact of Mother's Knowledge on The Success of Exclusive Breastfeeding - feva tridiyawati; Emsuarni Emsuarni (JOURNAL EDUCATIONAL OF NURSING(JEN), 2020)
Objective of this research is knowing the knowledge by the mother's behavior in the exclusive breastfeeding in infants at the hospital Evasari Jakarta in 2016. Research methodology used is analytic. Population in research it is a whole mother who the baby is that visit evasari jakarta hospital in january 2017, with the sample of the some 50 people. Based on the research done analysis univariat most among respondents who do not give breastfeeding exclusive (54.0%) and analysis bivariate knowledge show the connection with the behavior mother in the provision of breastfeeding exclusive in infants in a hospital evasari jakarta with the p = 0.004.